Long-term administration of escitalopram in patients with social anxiety disorder in Japan - Asakura S; Hayano T; Hagino A; Koyama T; Sasai S (Neuropsychiatric Disease and Treatment)
Satoshi Asakura,1 Taiji Hayano,2 Atsushi Hagino,2 Tsukasa Koyama3 1Health Care Center and Department of Psychiatry, Hokkaido University Graduate School of Medicine, Sapporo, Hokkaido, 2Clinical Development Planning and Management, Mochida Pharmaceutical Co., Ltd, Tokyo, 3Clinical Research Center, Oyachi Hospital, Sapporo, Hokkaido, Japan Purpose: To investigate the safety, tolerability, and effectiveness of escitalopram in patients with social anxiety disorder in Japan.Methods: A 52-week, open-label study was conducted in Japanese patients with social anxiety disorder with a total score ≥60 on the Liebowitz Social Anxiety Scale – Japanese Version (LSAS-J) and ≥4 on the Clinical Global Impression – Severity Scale. Escitalopram 10 mg/day was administered for the first week and could be increased to 20 mg/day.Results: The study included 158 patients: 81.0% (128/158) completed 52 weeks of escitalopram treatment, 68.4% (108/158) increased their dose to 20 mg/day, and 56.3% (89/158) remained on 20 mg/day. Adverse drug reactions were reported by 57.6% (91/158) of patients. The most common (incidence ≥10%) were somnolence and nausea. The incidence of adverse drug reactions was similar in extensive and poor metabolizers of cytochrome P450 2C19. No adverse drug reactions increased in incidence by >5% after week 12. The incidence of serious adverse events was 1.3% (2/158). No deaths occurred. The LSAS-J total scores improved until week 52. The LSAS-J response rate (≥30% improvement in LSAS-J) was 69.0%, the Clinical Global Impression – Improvement Scale response rate (≤2) was 73.0%, and the LSAS-J remission rate (≤30) was 27.0%.Conclusion: In this first 52-week clinical study of social anxiety disorder, escitalopram 10–20 mg/day was safe, well tolerated, and effective in Japanese patients. Keywords: escitalopram, Japanese, long-term study, social anxiety disorder, selective serotonin reuptake inhibitors